The Association of Age, Gender, and Carcinoembryonic Antigen (CEA) levels with Adenocarcinoma Grading in Patients with Colorectal Cancer - Sihombing Cicilia Yolanda (ITKES Wiyata Husada Samarinda, 2022)
Colorectal cancer is a malignancy that originates in the tissue of the large intestine, which can consist of the colon and/rectum. Colorectal cancer ranks fourth of all type of cancer cases in Indonesia. The most common type of colorectal cancer based on histopathology classification is adenocarcinoma. This study aimed to determine the association of age, gender and Carcinoembryonic Antigen (CEA) levels with adenocarcinoma grading in patients with colorectal cancer. This research design was observational analytic with a cross sectional study approach. This research data came from medical records of colorectal cancer patients at Abdul Wahab Sjahranie Hospital, Samarinda in 2017–2021. The sample of this study consisted of 138 patients who met the inclusion and exclusion criteria. The univariate analysis described frequency distribution and percentage of each variables. The bivariate analysis used the Chi-Square test. The result showed that the percentage of young and old patients were same (50,0%). Most of the patients were male (54,3%), had increased CEA levels (63,0%), and had low grade adenocarcinoma (86,2%). Data analysis of age with adenocarcinoma grading showed p=0,459. Data analysis of gender with adenocarcinoma grading showed p=0,005 and PR=1,211. Data analysis of CEA levels with adenocarcinoma grading showed p=0,011 and PR=2,924. Based on the results of the study, there is significant association of gender and CEA levels with adenocarcinoma grading in patients with colorectal cancer and there is no significant association of age with adenocarcinoma grading in patients with colorectal cancer.